The Effects of Chemical Disinfection on Dimensional Stability among Different Type of Impression Addition Silicon Materials - Salah A. Yousief; Khames T. Alzahrani; Suha M. Alhuwairini; Fai Y. Alharbi; Dalal A. Eissa; Sara M. Almojaddidi; Maha A. Almalki; Waad E. Alsulami; Waad K. Alsaiari; Abdullah J. Algharamah; et al. (International Journal of Innovative Research in Medical Science, 2020)
Introduction: Saliva and blood contaminated impressions are often a source of cross contamination between the clinic and dental laboratory. Explicit communication and observance of an infection control protocol for handling of dental impressions must exist among the office staff as well as between office and dental laboratories. Though disinfection of impression is routinely followed, autoclaving elastomeric impression is an effective method of sterilization them. Objectives: The purpose of this study was to evaluate dimensional stability and detail reproduction of a new addition silicon impression material after disinfection. Methods: In this study, a total of twenty impressions for the master model using heat resistant plastic stock trays. The twenty impressions were divided into two groups according to disinfection technique: (Table 2) Group 1: (n=10) Control group, untreated impressions. (C.G) Group 2: (n=10) Impressions were chemically disinfected. (D.G). after all impressions treatment, they were poured with extra hard stone (type IV) to get stone casts. Dimensional accuracy and detail reproduction of the impression material were evaluated indirectly through the recovered improved stone casts from impressions of the master model using the travelling microscope. Results: Cross arch distance (A): Epoxy resin master model cross arch distance measurement (A) was (41.36 mm). 1.1 Measurements of the cross-arch distance of stone casts Control group (C.G): The mean and standard deviation values of distance (A) in stone models obtained from C.G. were 41.553 ± 0.170 mm. Disinfection group (D.G): The mean and standard deviation values of distance (A) in stone models obtained from D.G were 41.368 ± 0.083 mm. ANOVA test showed that there was a statistically difference shrinkage between the groups (P-value = 0.006). 1.2 Measurement of the dimensional changes in the cross-arch distance of the different groups. The mean and standard deviation values of cross arch distance changes in stone models of C.G. were 0.191 ± 0.170 mm. while dimensional changes in stone models obtained from D.G. were 0.006 ± 0.082 mm. Conclusion: The purpose of this study was to evaluate dimensional stability and detail reproduction of a new addition silicon impression material after disinfection. In this study an epoxy resin master model was duplicated from a modified dentate mandibular model. Within the limitations of this study, it could be concluded that Chemical disinfectant of polyvinyl siloxane impression material can be successfully used in making fixed partial dentures.